WATERVERSE: Strategies in Stakeholder Engagement for the Digitalization of a Water Data Management Ecosystem - Mollie Torello; Siddharth Seshan; Suze van der Meulen; Lydia Vamvakeridou-Lyroudia (Engineering Proceedings)
WATERVERSE utilize Multi-Stakeholder Forums (MSFs) to engage diverse stakeholders from the water sector. Forums foster dialogue to establish a current state and future vision of data ecosystems. Upcoming forums will explores risks, barriers, opportunities, and governance needs. In the Netherlands pilot, PWN developed a chloride prediction model, using WDME for streamlined data processing and dashboard insights. This initial implementation demonstrates the WDME’s potential, addressing key stakeholder requirements and supporting data-driven water management decisions with future developments planned through 2025.